Pose Tracking, Analysis and Impact Estimation in Real Time - Katre, Yogesh; Singh, Abhinav; Meshram, Prashik; Sabri, Mohammed; Mesram, Pranjal; Bhave, Varsha (I-manager's Journal on Image Processing, 2025)
The present study introduces a user-friendly and highly effective push-up monitoring system that exploits camera technology and computer vision techniques to help in conducting workout routines. The system is able to evaluate the push-up form used by the target user, counts the number of repetitions done, and also provides feedback in real-time to ensure that the users maintain proper form while doing the exercise and avoid some common mistakes. This is a sure exercise program tool that will help the fitness enthusiast, trainer, or physiotherapist in improving exercises. It can be used for all types of environments, such as fitness centers, home workouts, and rehabilitation, offering a smart way to monitor progress and optimize training.